OPPORTUNITIES OF LOW-DOSE DIGITAL FLUOROGRAPHY IN DIAGNOSIS OF PHENOTYPIC VARIANTS OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE - N. A. Gorbunov; A. P. Dergilev; V. I. Kochura; Ya. L. Manakova; S. N. Volchenko; A. V. Sudarkina (Вестник рентгенологии и радиологии)
Objective. To determine the opportunities of low-dose digital fluorography (LDDF) in differential diagnosis of phenotypic variants of chronic obstructive pulmonary disease (COPD).Material and methods. There were 107 patients with clinically diagnosed COPD of varying severity examined. The average age of the patients was 51.8±1.5 years (46–59 years). All patients for LDDF of the chest in the frontal projection in the inspiratory and expiratory phase of respiration were undergone.Results. The electron optical density of the lungs was determined in the upper, middle and lower zones of both lungs. As a result in patients with a predominance of emphysematous variant of COPD (n=15) the most characteristic radiological symptom was lung hyperventilation (14% of 107 patients) and inspiratory electron optical density value was 748.18±4.72 optical density units (ODU). In patients with a predominance of bronchitic variant of COPD (n=43) the most common radiological symptom was the presence of symptom amplification and deformation of lung pattern (40% of 107 patients) and inspiratory electron optical density value was 668.04±12.26 ODU. For patients with mixed phenotypic variant of COPD (n=49) it was characterized by a combination of X-ray symptom amplification and deformation of lung pattern with lung emphysema (46% of 107 patients); the average value of inspiratory electron optical density value was 815.24±17.25 ODU.Conclusion. The technique of LDDF can detect X-ray symptoms and determine inspiratory and expiratory electron optical density of the lungs in patients with COPD that allows optimizing the differential diagnosis of phenotypic variants of chronic obstructive pulmonary disease.